Preparation method of ionized water gel with adjustable rigidity

By adding specific chemical substances to the solution of nanocellulose and other materials and induced secondary phase separation by ultraviolet irradiation and anhydrous ethanol replacement, an ionic hydrogel with adjustable stiffness was prepared, which solved the problem of the limited range of the existing hydrogel stiffness adjustment and difficulty in taking into account both toughness and rigidity, and achieved high fracture strength, strain ability and toughness, which was suitable for multi-field applications.

CN119708362APending Publication Date: 2025-03-28GUANGDONG SONGHENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967223.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing switchable mechanical properties hydrogels have problems such as limited stiffness adjustment range, difficulty in taking into account toughness and rigidity, and insufficient material stability and shape controllability when achieving responsive mechanical conversion.

Method used

Ionic hydrogels with adjustable stiffness were prepared by adding specific chemicals to a solution composed of nanocellulose, acrylic acid and acrylamide, and induced secondary phase separation by ultraviolet irradiation and anhydrous ethanol replacement.

Benefits of technology

It achieves a large stiffness switching, improves the fracture strength, strain ability and toughness of the material, and ensures the stability and controllability of the material in response to stimuli. It is suitable for the fields of armor equipment, bionic smart materials, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708362A_ABST
    Figure CN119708362A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer materials for adjusting rigidity through phase change, in particular to a preparation method of rigidity-adjustable ionized water gel. The preparation method comprises the following steps: adding zinc trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, N, N '-methylene bisacrylamide and 2-hydroxy-2-methyl-1-phenylacetone into a solution consisting of nano cellulose, acrylic acid and acrylamide, so as to obtain an ionized water gel precursor solution; irradiating the precursor solution by adopting ultraviolet light to obtain soft ionized water gel; and soaking the soft ionized water gel in an absolute ethyl alcohol solution, and controlling the soaking time to obtain the rigidity-adjustable ionized water gel. Reversible switching between the soft-state ionized water gel and the rigid plastic can be achieved according to requirements without adopting complex procedures, the switching range reaches 104, and the method can be applied to the frontier fields such as defense equipment, bionic intelligent materials, soft robots and biomedical equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology with adjustable stiffness through phase change, and in particular to a method for preparing an ionic hydrogel with adjustable stiffness. Background Technology

[0002] The mechanical duality of responsive polymer materials with variable mechanical properties offers a solution to the engineering paradox of shape adaptability and load-bearing capacity. By adjusting their mechanical properties, they can soften when needed to adapt to complex environments or surfaces, providing good shape adaptability, while simultaneously enhancing hardness and strength under specific conditions to ensure sufficient load-bearing capacity. These materials utilize mechanical duality to exhibit different mechanical behaviors under different conditions, such as achieving transitions from soft to hard, localized strengthening, and intelligent response—that is, automatically adjusting properties according to external conditions—thus optimizing the functionality and efficiency of the structure without human intervention.

[0003] Despite advancements in design strategies for switchable mechanical properties hydrogels, significant challenges remain. These challenges stem from the complex molecular structure and chemical modification requirements, as well as the inherent limitations in mechanical strength inherent in switchable mechanical property hydrogels. During the process of achieving responsive mechanical switching, polymer networks often exhibit instability, such as susceptibility to decomposition or structural collapse. This not only makes volume and morphology control difficult but also limits the improvement of their mechanical properties. An ideal switchable mechanical property hydrogel system should exhibit a wide range of stiffness tuning, as a larger stiffness variation (ideally exceeding 2–4 orders of magnitude) would significantly enhance its applicability and functionality across multiple fields. In contrast, most current systems are limited to stiffness variations of only 1 to 2 orders of magnitude, which is clearly restrictive. Furthermore, although some research has reached stiffness-switching gel materials with variations up to 5 orders of magnitude, this achievement masks another core problem: in pursuing ultimate stiffness tuning, materials often have to compromise between stiffness and toughness. This trade-off becomes a key bottleneck hindering the comprehensive optimization of material properties.

[0004] Therefore, how to expand the range of stiffness adjustment without sacrificing toughness, while ensuring the stability and shape controllability of the material in response to stimuli, is a core problem that urgently needs to be solved in the current research on hydrogels with switchable mechanical properties. Summary of the Invention

[0005] Based on the above, this invention provides a method for preparing an ionic hydrogel with adjustable stiffness. The ionic hydrogel prepared using this method can achieve a wide range of stiffness adjustments.

[0006] To achieve the above objectives, the present invention provides the following solution:

[0007] One of the technical solutions of this invention is a method for preparing an ionic hydrogel with adjustable stiffness, comprising the following steps:

[0008] Zinc trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, N,N'-methylenebisacrylamide and 2-hydroxy-2-methyl-1-phenylpropanone were added to a solution composed of nanocellulose, acrylic acid and acrylamide to obtain an ion hydrogel precursor solution.

[0009] The precursor solution was irradiated with ultraviolet light to obtain a soft ionic hydrogel;

[0010] The soft ionic hydrogel was immersed in anhydrous ethanol, and the immersion time was controlled to obtain the ionic hydrogel with adjustable stiffness.

[0011] Furthermore, the nanocellulose is prepared by the following method: 100.0g of pulp is prepared into a 1.0% concentration suspension, poured into a zeroed ultrafine grinding mill, and the rotation speed is set to 2500rpm. The grinding disc gap and grinding number are +50μm (5 times), +20μm (5 times), 0μm (10 times), -20μm (10 times), -50μm (10 times), -50μm (10 times), -80μm (10 times) and -100μm (10 times), respectively, to obtain nanocellulose.

[0012] Further, the mass ratio of the nanocellulose, acrylic acid, acrylamide, zinc trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, N,N'-methylenebisacrylamide and 2-hydroxy-2-methyl-1-phenylpropanone is 0.072:2.25:3.75:2.5:2:0.01:0.02.

[0013] Furthermore, the wavelength of the ultraviolet light is 395 nm, and the irradiation time is 10 min.

[0014] Furthermore, the soft ionic hydrogel was soaked in anhydrous ethanol for 1-24 hours.

[0015] The present invention discloses the following technical effects:

[0016] To address the issues of limited stiffness switching range and incompatibility between strength and toughness in hydrogels, this invention prepares an ionic hydrogel material and induces secondary phase separation through a water and ethanol replacement strategy. This achieves a responsive gel material with an ultra-wide stiffness variation range, forming a polymer material with high fracture strength, high strain, high toughness, excellent energy dissipation performance, and good tolerance to cuts. This material can be applied in cutting-edge fields such as protective gear, biomimetic intelligent materials, soft robots, and biomedical devices. Furthermore, the material preparation is simple, the production process is highly repeatable, and it has the potential for large-scale production. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is the tensile stress-strain curve of the soft ionic hydrogel of the present invention.

[0019] Figure 2 The tensile stress-strain curve of the soft ionic hydrogel of the present invention is obtained after 50 cycles of tensile strain at a tensile strain of 500%.

[0020] Figure 3 The compression stress-strain curve of the soft ionic hydrogel of the present invention under 50 cycles of compression at a compression strain of 70%.

[0021] Figure 4 This is the tensile stress-strain curve of the tough ionic hydrogel of the present invention.

[0022] Figure 5 The tensile stress-strain curves of the tough ionic hydrogel of the present invention are obtained after 5 cycles of tensile stretching under tensile strains of 100%, 200%, and 300%.

[0023] Figure 6 This is the tensile stress-strain curve of the notched, tough ionic hydrogel of the present invention.

[0024] Figure 7 This invention presents the original hardened ionic hydrogel and its tensile stress-strain curves under different environmental tests.

[0025] Figure 8 The storage modulus and loss modulus of the rigid ionic hydrogel of this invention at the nanoscale are given.

[0026] Figure 9 This is the bending stress-strain curve of the rigid ionic hydrogel of the present invention. Detailed Implementation

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] Those skilled in the art will readily understand that various improvements and variations can be made to the specific embodiments of the present invention without departing from the spirit and scope thereof. Furthermore, other embodiments derived from the present invention are also readily apparent. Please note that the specification and embodiments of the present invention are provided as examples only.

[0029] The present invention will be further illustrated by the following examples.

[0030] Example 1

[0031] (1): Preparation of nanocellulose (CNFs)

[0032] 100.0g of pulp was prepared into a 1.0% concentration suspension and poured into a zeroed ultrafine grinding mill, with the rotation speed set to 2500rpm. The grinding disc gap and grinding number were +50μm (5 times), +20μm (5 times), 0μm (10 times), -20μm (10 times), -50μm (10 times), -50μm (10 times), -80μm (10 times), and -100μm (10 times) to obtain nanocellulose.

[0033] (2): Preparation of soft ionic hydrogels

[0034] Take 6g of the nanocellulose solution prepared in step (1), add 2.25g of acrylic acid and 3.75g of acrylamide, stir at 400rpm for 10min, then add 2.5g of zinc trifluoromethanesulfonate and 2g of 1-ethyl-3-methylimidazolium tetrafluoroborate, and continue stirring for 30min to mix the solution evenly. Then add the crosslinking agent N,N'-methylenebisacrylamide and the photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone to the mixture, and stir for 10min to obtain the ionized hydrogel precursor solution. Add the ionized hydrogel precursor solution to a polytetrafluoroethylene mold, and perform photoinitiated graft copolymerization using a UV curing lamp with a wavelength of 395nm for 10min. A regular soft ionized hydrogel is obtained.

[0035] Example 2

[0036] (1): Preparation of nanocellulose (CNFs)

[0037] 100.0g of pulp was prepared into a 1.0% concentration suspension and poured into a zeroed ultrafine grinding mill, with the rotation speed set to 2500rpm. The grinding disc gap and grinding number were +50μm (5 times), +20μm (5 times), 0μm (10 times), -20μm (10 times), -50μm (10 times), -50μm (10 times), -80μm (10 times), and -100μm (10 times) to obtain nanocellulose.

[0038] (2): Preparation of soft ionic hydrogels

[0039] Take 6g of the nanocellulose solution prepared in step (1), add 2.25g of acrylic acid and 3.75g of acrylamide, stir at 400rpm for 10min, then add 2.5g of zinc trifluoromethanesulfonate and 2g of 1-ethyl-3-methylimidazolium tetrafluoroborate, and continue stirring for 30min to mix the solution evenly. Then add the crosslinking agent N,N'-methylenebisacrylamide and the photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone to the mixture, and stir for 10min to obtain the ionized hydrogel precursor solution. Add the ionized hydrogel precursor solution to a polytetrafluoroethylene mold, and perform photoinitiated graft copolymerization using a UV curing lamp with a wavelength of 395nm for 10min. A regular soft ionized hydrogel is obtained.

[0040] (3): Preparation of ionized hydrogels with adjustable stiffness

[0041] Take the soft ionic hydrogel prepared in step (2) and immerse it in anhydrous ethanol for 4 hours to obtain a tough ionic hydrogel.

[0042] Example 3

[0043] (1): Preparation of nanocellulose (CNFs)

[0044] 100.0g of pulp was prepared into a 1.0% concentration suspension and poured into a zeroed ultrafine grinding mill, with the rotation speed set to 2500rpm. The grinding disc gap and grinding number were +50μm (5 times), +20μm (5 times), 0μm (10 times), -20μm (10 times), -50μm (10 times), -50μm (10 times), -80μm (10 times), and -100μm (10 times) to obtain nanocellulose.

[0045] (2): Preparation of soft ionic hydrogels

[0046] Take 6g of the nanocellulose solution prepared in step (1), add 2.25g of acrylic acid and 3.75g of acrylamide, stir at 400rpm for 10min, then add 2.5g of zinc trifluoromethanesulfonate and 2g of 1-ethyl-3-methylimidazolium tetrafluoroborate, and continue stirring for 30min to mix the solution evenly. Then add the crosslinking agent N,N'-methylenebisacrylamide and the photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone to the mixture, and stir for 10min to obtain the ionized hydrogel precursor solution. Add the ionized hydrogel precursor solution to a polytetrafluoroethylene mold, and perform photoinitiated graft copolymerization using a UV curing lamp with a wavelength of 395nm for 10min. A regular soft ionized hydrogel is obtained.

[0047] (3): Preparation of ionized hydrogels with adjustable stiffness

[0048] Take the soft ionic hydrogel prepared in step (2) and immerse it in anhydrous ethanol for 24 hours to obtain a hard ionic hydrogel.

[0049] The tensile stress-strain curve of the soft ionic hydrogel prepared in this invention is as follows: Figure 1 As shown, its fracture strength is 1793.97 kPa and its fracture strain is 741.53%, indicating that the soft ionic hydrogel has good mechanical properties.

[0050] Figure 2 This is the tensile stress-strain curve of the soft ionic hydrogel of the present invention under 500% tensile strain after 50 cycles of cyclic stretching. In the first load-unload cycle, the soft ionic hydrogel exhibits a significant hysteresis effect. From the second cycle to the fiftieth cycle, the hysteresis loops of the soft ionic hydrogel almost completely overlap. This reveals that the material rapidly adapts to high strain conditions after the initial cycle, subsequently exhibiting excellent cyclic stability and durability. Its internal structure can efficiently and continuously respond to external mechanical stress, maintaining stable mechanical properties.

[0051] Figure 3 This document presents the compressive stress-strain curves of the soft ionic hydrogel of this invention under 50 cycles of compression at a compressive strain of 70%. The compressive stress-strain curves for each cycle exhibit high consistency, revealing the excellent cyclic stability and reversibility of the soft ionic hydrogel under significant compressive deformation. This indicates that the material possesses extremely low plastic deformation accumulation and excellent structural recovery capability under repeated compressive loads.

[0052] Figure 4 This is the tensile stress-strain curve of the tough ionic hydrogel of this invention. The tough ionic hydrogel exhibits strong and tough properties, with a fracture strength of 13.82 MPa and a fracture strain maintained at 389%. This allows the tough ionic hydrogel to not only withstand high stress but also maintain structural integrity under large deformation. Simultaneously, the tough ionic hydrogel has a Young's modulus of 436.17 MPa, indicating a certain degree of rigidity. Combined with its high fracture strain, this gives the tough ionic hydrogel excellent impact resistance.

[0053] Figure 5This invention presents the tensile stress-strain curves of the tough ionic hydrogel under 5 cyclic stretching cycles at tensile strains of 100%, 200%, and 300%. The first cycle exhibits a large residual strain, which typically indicates that significant microstructural rearrangement occurred within the tough ionic hydrogel after the initial loading to above the yield point. This results in permanent deformation of the material's internal structure, which cannot fully recover to its original state even after unloading, leaving significant residual strain. From the second cycle onwards, the tough ionic hydrogel exhibits slow stress growth in the lower strain range due to the lack of recovery of residual strain. With further increases in strain, the stress-strain relationship begins to show an approximately linear relationship. The tough ionic hydrogel exhibits excellent energy dissipation (30.83 MJ / m²) at 300% strain. 3 ) and large residual strain (246%) after unloading.

[0054] Figure 6 This is the tensile stress-strain curve of the notched, tough ionic hydrogel of this invention. A standardized 5mm notch (total width 10mm) was created at the center of the tough ionic hydrogel to simulate its toughness changes and crack propagation resistance. After introducing the notch, the fracture strength of the tough ionic hydrogel decreased to 8.65MPa, the fracture strain decreased to 121.87%, and the fracture energy decreased to 8.9kJ / m. 2 Although the cutting process leads to a decrease in the mechanical properties of the tough ionic hydrogel, it still maintains relatively high toughness and energy absorption capacity, and does not undergo brittle fracture, indicating that it has the ability to resist crack propagation.

[0055] Figure 7 This paper presents the original rigid ionic hydrogel of this invention and its tensile stress-strain curves under different environmental tests. The tensile strength of the rigid ionic hydrogel reaches 26.52 MPa, which is 25 times higher than that of the soft ionic hydrogel. The Young's modulus of the rigid ionic hydrogel is also as high as 676.99 MPa, which is 1930 times that of the soft ionic hydrogel. The changes in the mechanical properties of the rigid ionic hydrogel after 30 days of storage under three typical environmental conditions indicate that the material exhibits good mechanical stability over a wide temperature range.

[0056] Figure 8 This invention presents the storage modulus and loss modulus of the rigid ionic hydrogel at the nanoscale. The storage modulus of the rigid ionic hydrogel ranges from 320 MPa to 400 MPa across different frequency ranges. Simultaneously, its storage modulus and loss modulus range from 54 to 85 MPa across different frequency ranges, further emphasizing the efficient energy dissipation capability of the rigid ionic hydrogel under dynamic loading.

[0057] Figure 9This is the bending stress-strain curve of the rigid ionic hydrogel of this invention. No cracks were observed in the rigid ionic hydrogel after experiencing significant bending strain (reaching 16.00%). This highlights the unique ability of the rigid ionic hydrogel to maintain a balance between elasticity and plasticity, preserving continuity even under extreme bending strain conditions.

Claims

1. A method for preparing an ionic hydrogel with adjustable stiffness, characterized in that: The steps include: S1, adding zinc trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, N,N'-methylenebisacrylamide and 2-hydroxy-2-methyl-1-phenylacetone to a solution consisting of nanocellulose, acrylic acid and acrylamide to obtain an ionic hydrogel precursor solution; S2, irradiating the precursor solution with ultraviolet light to obtain a soft ionic hydrogel; S3, soaking the soft ionic hydrogel in anhydrous ethanol, controlling the soaking time, and obtaining the ionic hydrogel with adjustable stiffness.

2. The method for preparing an ionic hydrogel with adjustable stiffness according to claim 1, characterized in that: The mass ratio of nanocellulose, acrylic acid, acrylamide, zinc trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium tetrafluoroborate, N,N'-methylenebisacrylamide and 2-hydroxy-2-methyl-1-phenylacetone in the ionic hydrogel precursor solution is 0.072:2.25:3.75:2.5:2:0.01:0.

02.

3. The method for preparing an ionic hydrogel with adjustable stiffness according to claim 1, characterized in that: The wavelength of the ultraviolet light in step S2 is 395 nm, and the corresponding irradiation time is 10 min.

4. The method for preparing an ionic hydrogel with adjustable stiffness according to claim 1, characterized in that: In step S3, the soft ionic hydrogel is immersed in anhydrous ethanol for 1-24 hours.

5. A method for preparing an ionic hydrogel with adjustable stiffness, characterized in that: The ionic hydrogel with adjustable stiffness is prepared by the preparation method according to any one of claims 1 to 4.

6. Application of the ionic hydrogel with adjustable stiffness according to claim 5 in the fields of protective equipment, bionic intelligent materials, soft robots or biomedical equipment.